Minimally invasive hybrid retrieval of a fractured sion guidewire during transcatheter coronary intervention: a case report of multidisciplinary collaborative management - Xianliang Dai; Jiming Han; Yijing Guo; Gang Zhao; Chengxing Shen (Frontiers in Cardiovascular Medicine, 2026)
Background Guidewire fracture during percutaneous coronary intervention (PCI) is rare but serious, with management dependent on fracture characteristics. We report an innovative minimally invasive hybrid approach for this complication. Case summary A 59-year-old male with diabetes/hypertension developed Sion guidewire fracture during LAD PCI. Percutaneous retrieval failed; conservative therapy was initially given. A minimally invasive hybrid “trans-brachial arteriotomy with endoluminal traction” retrieved the fragment 34 days post-fracture, with uneventful recovery. Discussion Guidewire fracture occurs in 0.2%–0.8% of PCI cases. Histopathological evidence suggests that at 34 days, incomplete endothelialization facilitates rather than hinders retrieval. Although no standard retrieval window exists, delayed elective retrieval can achieve high success rates in stable patients. Traditional open surgery is traumatic; our hybrid approach avoids sternotomy, offering a novel salvage strategy valuable for interventional cardiologists and surgeons. Take home messages Minimally invasive hybrid retrieval is safe and effective for PCI guidewire fractures refractory to percutaneous methods, emphasizing the value of multidisciplinary collaboration.